Rima Akhir Bait-Bait Puisi Arab Perspektif Ilmu Qawâfi - Akhmad Patah (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
This paper aims to describe the concept of qâfiyah according to experts and its function in Arabic poetry. This research uses a qualitative descriptive approach with a type of literature study. Primary data sources come from several diwan books, and secondary data sources come from several books on the science of 'Arudl and Qâfiyah books, journals, or other research related to this theme—data collection using the method of literature and analysis with descriptive content analysis techniques. The results of the study show that in each qâfiyah, there are raw letters that are constantly repeated and function to bind the similarity and harmony of the final sound of a qasida, plus there are also supporting letters and vowels which are used as benchmarks for qâfiyah harmony. The final rhyme, or qâfiyah, has an aesthetic function for Arabic poetry, complementing other aesthetic elements such as wazan and the various dimensions or Bahr patterns. The monotonous qâfiyah pattern is the one most chosen by Arab poets. In addition, aesthetic value also arises from the existence of qâfiyah muzdawij (paired) and qâfiyah musyath-thar (patterns), which display one qasida with several qâfiyah variations according to the number of lines desired by the poet. Abstrak Tulisan ini bertujuan untuk mendeskripsikan bagaimana konsep qâfiyah menurut para ahlinya dan apa fungsinya dalam puisi Arab. Penelitian ini menggunakan pendekatan kualitatif dekriptif dengan jenis studi kepustakaan. Sumber data primer berasal dari beberapa kitab diwan para pujangga Arab kuno dan sumber data sekunder berasal dari beberapa kitab mengenai ilmu ‘Arudl dan kitab Qâfiyah, jurnal atau penelitian lain yang terkait dengan tema ini. pengumpulan data menggunakan metode kepustakaan dan dianalisis dengan teknik content analysis deskriptif. Hasil penelitian menunjukkan bahwa pada setiap qâfiyah terdapat huruf rawi yang selalu diulang-ulang dan berfungsi untuk mengikat kesamaan dan keserasian bunyi akhir bait suatu qashidah, ditambah juga terdapat juga huruf-huruf pendukung dan harakatnya yang dijadikan tolok ukur keserasian qâfiyah. Untuk syair Arab, rima akhir atau qâfiyah berfungsi estetis, melengkapi unsur estetis lainnya seperti wazan dan pola matra atau bahr dengan berbagai macamnya. Pola qâfiyah yang monoton adalah yang paling banyak dipilih oleh para penyair Arab, Selain itu, nilai estetis juga muncul dari adanya pola qâfiyah muzdawij (berpasangan) dan musyath-thar yang menampilkan satu qashidah dengan beberapa variasi qâfiyah sesuai dengan jumlah baris yang dikehendaki oleh penyair. .